High temperature friction and wear mechanism map for tool steel and boron steel tribopair. (June 2014) - Hernandez, S.; Hardell, J.; Courbon, C.; Winkelmann, H.; Prakash, B.
<x content-type="archive" xml:space="preserve">Abstract</x> Tribological systems working under severe conditions like high pressures, sliding velocities and temperatures are subjected to different phenomena such as wear, oxidation and changes in mechanical properties. In many cases, there are several mechanisms occurring simultaneously. The predominating type(s) of wear mechanism(s) presented will depend on the materials in contact, operating parameters and surrounding environment. In this work, high temperature tribological studies of boron steel sliding against tool steel were conducted using a pin-on-disc machine under unlubricated conditions at five different temperatures ranging from 25 to 400°C, three different loads: 25, 50 and 75 N (contact pressures of 2, 4 and 6 MPa respectively) and a sliding speed of 0·2 ms−1. Scanning electron microscopy/energy dispersive spectroscopy and X-ray techniques were used for analysing the resulting damage and tribolayers of the worn surfaces. Additionally, hardness measurements were carried out in a special hot hardness rig in the same temperature range as that used in pin-on-disc tests. The results have shown that for a given load, the wear rate of boron steel decreased as the temperature increased, reaching its lowest value at 400°C at 50 N. In the case of the tool steel, it could be observed that at 200°C and above, the wear rate decreased as the load increased. This behaviour is consistent with the formation of a protective oxidised layer initiated at 100°C. At higher temperatures, such layers become more pronounced. The obtained data were finally used to construct a friction and wear mechanism map for this material pair that takes temperature and pressure into account.